New Directions in Digital Terminology Research - Martín, Antonio San; Faber, Pamela; Sánchez-Cárdenas, Beatriz; Vezzani, Federica; Nunzio, Giorgio Di (Lexicography, Terminology, and Society, 2026)
How can digital terminology rise to the challenges of a multilingual, interconnected world? This book offers concrete answers through cutting-edge case studies that combine user-centered design, ontologies, chatbots, and generative AI. You will explore how generative AI tools can support terminology work, how cultural heritage is preserved through structured terminological resources, and how tools are developed to support both experts and everyday users. Featuring practical methodologies, innovative uses of technology, and a focus on accessibility and interoperability, this volume is an essential resource for anyone working in terminology, lexicography, translation studies, corpus linguistics, language technology, and digital humanities.